2022
DOI: 10.1002/aur.2726
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of the simplified Chinese version of the Social Communication Questionnaire

Abstract: This study aims to validate the simplified Chinese version of the Social Communication Questionnaire (SCQ) in children aged 2–12 years from both general and clinical populations. We recruited 819 Chinese children in this study, including 505 typically developing (TD) children, 202 children with autism spectrum disorder (ASD) and 112 children with non‐ASD neurodevelopmental disorders. All the children's parents completed the simplified Chinese version of the SCQ and all children with ASD were additionally asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Furthermore, our study evaluated the four‐factor structure, which has been used in the original instrument (Berument et al, 1999) and which maps onto the three DSM‐IV domains. This approach is consistent with some recent cross‐linguistic adaptations of SCQ (Arabic: Aldosari et al 2019; simplified Chinese: Liu et al, 2022). Additionally, we considered a two‐factor structure, consistent with the two domains of DSM‐5 (the S‐ and R‐ domains discussed in Liu et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Furthermore, our study evaluated the four‐factor structure, which has been used in the original instrument (Berument et al, 1999) and which maps onto the three DSM‐IV domains. This approach is consistent with some recent cross‐linguistic adaptations of SCQ (Arabic: Aldosari et al 2019; simplified Chinese: Liu et al, 2022). Additionally, we considered a two‐factor structure, consistent with the two domains of DSM‐5 (the S‐ and R‐ domains discussed in Liu et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…This approach is consistent with some recent cross‐linguistic adaptations of SCQ (Arabic: Aldosari et al 2019; simplified Chinese: Liu et al, 2022). Additionally, we considered a two‐factor structure, consistent with the two domains of DSM‐5 (the S‐ and R‐ domains discussed in Liu et al, 2022). Our results suggested that the fit of the four‐factor model was better than that of the two‐factor model, with the fit of the latter being at the margins of acceptability thresholds.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations